Characteristics of depressive and bipolar disorder patients with mixed features. (3rd June 2018) - Tondo, L.; Vázquez, G. H.; Pinna, M.; Vaccotto, P. A.; Baldessarini, R. J.
Abstract : Objective: To assess differences between subjects with vs. without mixed features in major affective disorders. Methods: In 3099 out‐patient subjects with DSM‐5 major depressive disorder (MDD, n  = 1921) or bipolar disorders (BD, n  = 1178), we compared those with (Mx) vs. without (Non‐Mx) mixed features (agitated‐irritable depression or dysphoric [hypo]mania) in an index episode. Results: Prevalence of Mx averaged 21.9% [CI: 20.5–23.4] overall, ranking: BD‐II > BD‐I > MDD, and in BD depression ≥ [hypo]mania > MDD. Mx subjects were significantly more likely than Non‐Mx cases to (i) have other mixed episodes, (ii) have higher irritable and agitated ratings, (iii) have more substance abuse, (iv) switch into mixed episodes, (v) have more suicide attempts and higher suicidal ratings, (vi) change diagnosis from depression to BD, (vii) have higher hypomania scores when depressed or depression scores when [hypo]manic, (viii) be unmarried or separated with fewer children and siblings, (ix) be diagnosed more with BD than MDD, (x) be unemployed, (xi) have BD, suicide and divorce among first‐degree relatives, (xii) be female, (xiii) be younger at illness‐onset. Both BD and MDD Mx subjects also received antidepressants less, but antipsychotics and mood‐stabilizers more, alone and in combination with antidepressants. Conclusions: Mood disorder subjects with agitated‐irritable depression or dysphoric [hypo]mania differed from those without such mixed features, including having a less favorable clinical course and repeated mixed episodes. They may represent a distinct and prevalent, syndromal clinical subtype with prognostic and therapeutic significance.